2022
DOI: 10.1155/2022/2897338
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of FLOT2 Gene Expression on Invasion and Metastasis of Colorectal Cancer and Its Molecular Mechanism under Nanotechnology and RNA Interference

Abstract: The study is aimed at investigating the effect of the FLOT2 gene on invasion and metastasis of colorectal cancer (CRC) cells and the corresponding molecular mechanism by preparing polylysine-silicon nanoparticles. Specifically, polylysine was used to modify the silica nanoparticles prepared by the emulsification method to obtain polylysine-silicon nanoparticles. The characterization of polylysine-silicon nanoparticles was completed by nanoparticle size analyzer, laser particle size potentiometer, and transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recent some studies have displayed that higher expression of FLOT2 is associated with the aggravation of several human cancers. For instance, silencing of FLOT2 suppresses the CRC cell invasion and migration [ 27 ]. In addition, the TBL1X/FLOT2 positive feedback loop strengthened metastasis in nasopharyngeal carcinoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent some studies have displayed that higher expression of FLOT2 is associated with the aggravation of several human cancers. For instance, silencing of FLOT2 suppresses the CRC cell invasion and migration [ 27 ]. In addition, the TBL1X/FLOT2 positive feedback loop strengthened metastasis in nasopharyngeal carcinoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Fungal diversity was examined via the ITS method. [ 17 ] These procedures were performed as follows: (1) bacterial DNA and fungal RNA were extracted from the mold culture samples; (2) the universal primers of the bacterial DNA and the fungal RNA were added and PCR amplified; and (3) base sequences were tested, and bacterial genus was identified through evolutionary tree analysis. The percentage of each colony was calculated on the basis of its copy number.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%